Cytokine production by infrapatellar fat pad can be stimulated by interleukin 1β and inhibited by peroxisome proliferator activated receptor α agonist. Issue 6 (2nd February 2012) - Clockaerts, Stefan; Bastiaansen-Jenniskens, Yvonne M; Feijt, Carola; De Clerck, Luc; Verhaar, J A N; Zuurmond, Anne-Marie; Stojanovic-Susulic, Vedrana; Somville, Johan; Kloppenburg, Margreet; van Osch, Gerjo J V M
Abstract : Background: Infrapatellar fat pad (IPFP) might be involved in osteoarthritis (OA) by production of cytokines. It was hypothesised that production of cytokines is sensitive to environmental conditions. Objectives: To evaluate cytokine production by IPFP in response to interleukin (IL)1β and investigate the ability to modulate this response with an agonist for peroxisome proliferator activated receptor α (PPARα), which is also activated by lipid-lowering drugs such as fibrates. Methods: Cytokine secretion of IPFP was analysed in the medium of explant cultures of 29 osteoarthritic patients. IPFP (five donors) and synovium (six donors) were cultured with IL-1β and PPARα agonist Wy14643. Gene expression of IL-1β, monocyte chemoattractant protein (MCP1), (IL-6, tumour necrosis factor (TNF)α, leptin, vascular endothelial growth factor (VEGF), IL-10, prostaglandin-endoperoxide synthase (PTGS)2 and release of TNFα, MCP1 and prostaglandin E2 were compared with unstimulated IPFP and synovium explants. Results: IPFP released large amounts of inflammatory cytokines, adipokines and growth factors. IL-1β increased gene expression of PTGS2, TNFα, IL-1β, IL-6 and VEGF and increased TNFα release in IPFP. MCP1, leptin, IL-10 gene expression and MCP1, leptin and PGE2 release did not increase significantly. Synovium responded to IL-1β similarly to IPFP, except for VEGF gene expression. Wy14643 decreased gene expression of PTGS2, IL-1β, TNFα, MCP1, VEGF and leptin in IPFP explants and IL-1β, TNFα, IL-6, IL-10 and VEGF in synovium that responded to IL-1β. Conclusion: IPFP is an active tissue within the joint. IPFP cytokine production is increased by IL-1β and decreased by a PPARα agonist. The effects were similar to effects seen in synovium. Fibrates may represent a potential disease-modifying drug for OA by modulating inflammatory properties of IPFP and synovium.